A framework for establishing industrial effluent limits with application to the iron and steel industry in Iran - Mahjouri, Maryam (2018)
The establishment of Emission Limit Values (ELVs), especially in the industrial sector, is one of the most problematic environmental issues in developing countries. In addition, industrial effluent limitations should be established regarding the special characteristics of each sector. In Iran, with a uniform “Wastewater Effluent Standard”, a scientific methodology for determining ELVs at the sector level is an essential need. The objective of this study is to present a reliable and pragmatic methodology for establishing ELV thresholds at the sector level with an emphasis on the Best Available Technology (BAT) concept. In general, the most common approach for technology evaluation and ELVs identification, in both developed and developing countries, is expert judgment. Therefore, this research employs a multi-dimensional approach. A hybrid Fuzzy multiple-criteria decision-making (FMCDM), consisting of the Analytic Hierarchy Process (AHP) and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) in combination with fuzzy logic is structured to make use of the combined benefits of several methods. The modelling framework includes three main sections that is: a) determining the most appropriate Wastewater Treatment Technologies (WTTs); b) computing the emission levels associated with the Best Practicable Control Technology Currently Available (BPT) concept; and c) identifying the final ELVs based on the results of the two previous sections. Iran’s iron and steel industry, which constitutes a fundamental sector in the country’s economy, is selected as the case study. The results obtained indicate that experts have considered the country-specific information, which consists of the most appropriate WTTs and ELVs related to BPT, as a reliable reference in their decisions. According to the findings, corrective measures in accordance with the BAT considerations should be implemented in many of the plants under consideration and the experts largely prefer the more advanced WTTs, because of their high system efficiency and compatibility with environmental impact criteria. This transparent stepwise process has resulted in defensible country-specific ELVs for the iron and steel industry, which can be developed for other sectors. As the main conclusion, this study demonstrates that FMCDM is a systematic and robust operational decision tool for this comprehensive assessment regarding the data availability limitations in developing countries and emphasises industrial sustainability. This hybrid model of AHP, TOPSIS and Fuzzy logic offers better results and provides a higher degree of confidence for this sophisticated judgment. It is a multi-dimensional approach that considers the sector characteristics; the interaction of the technical, environmental and economic aspects; and the specific preferences in developing countries.